2020
DOI: 10.1002/med.21742
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing hyperuricemia to atherosclerosis and understanding its mechanistic dependence

Abstract: Atherosclerosis is regarded as the disease of the arterial vasculature. The main characteristics of atherosclerosis are the abnormal accumulation of lipids, increased inflammatory cells, matrix deposits, and proliferation of smooth muscle cells. Diabetes mellitus, obesity, and hyperlipidemia are the most studied risk factors of atherosclerosis. One least studied risk factor is the uric acid (UA), a high UA in circulation is interlinked with many pathological processes. Several epidemiological studies suggest e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 74 publications
(145 reference statements)
1
50
0
Order By: Relevance
“…Hyperuricemia (HUA) is a metabolic disease caused by abnormal purine metabolism or insufficient uric acid (UA) excretion, characterized by elevated UA in the blood (Borghi, 2017;Dehlin et al, 2020). Previous studies report that HUA is highly related to hypertension, hyperlipidemia, fatty liver, diabetes, and other diseases (Wang et al, 2014;Jaruvongvanich et al, 2017;Jayachandran and Qu, 2020;Kielstein et al, 2020). With improvement of people's living standard and change of dietary pattern, incidence of HUA is increasing in recent years (Liu et al, 2014;Singh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperuricemia (HUA) is a metabolic disease caused by abnormal purine metabolism or insufficient uric acid (UA) excretion, characterized by elevated UA in the blood (Borghi, 2017;Dehlin et al, 2020). Previous studies report that HUA is highly related to hypertension, hyperlipidemia, fatty liver, diabetes, and other diseases (Wang et al, 2014;Jaruvongvanich et al, 2017;Jayachandran and Qu, 2020;Kielstein et al, 2020). With improvement of people's living standard and change of dietary pattern, incidence of HUA is increasing in recent years (Liu et al, 2014;Singh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…36 T2DM and hyperuricemia have been identified as an important risk factor for atherosclerosis. 11,22 However, whether sitagliptin treatment affects CIMT in T2DM patients with hyperuricemia has not been revealed.…”
Section: Discussionmentioning
confidence: 99%
“… 36 T2DM and hyperuricemia have been identified as an important risk factor for atherosclerosis. 11 , 22 However, whether sitagliptin treatment affects CIMT in T2DM patients with hyperuricemia has not been revealed. Although many clinical studies have shown that serum uric acid levels are correlated with CIMT, a marker of subclinical atherosclerosis, few studies have been conducted in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular diseases (CVDs) are among the most common causes of death globally, with hyperlipidemia representing one of its main risk factors ( Mahdavi et al, 2020 ; Jayachandran and Qu, 2021 ). In Herman-Lara et al (2014) evaluation of the protective activity of micronized insoluble fiber from the bagasse of A. carambola as an ingredient of a functional food (FF) or as micronized insoluble fiber-rich fraction (IFRF) and its effects in vivo on lipid metabolism in a murine model, serum TG, TC, HDL-C, and LDL-C decreased after a murine model was treated with IFRF and FF, with corresponding inhibition rates of 14.2, 25.4, 55.06, and 12.18% by IFRF, and 30.18, 39.47, 35.11, and 43.18% by FF.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%